Developments in food proteins. - Hudson, B. J. F. (London Elsevier, 1982)
Irregular.
Editor: B.J.F. Hudson.
Keywords: Proteins in human nutrition -- Periodicals; Food industry and trade -- Periodicals; Food -- Protein content -- Periodicals